Visualization of landscape changes and threatening environmental processes using a digital landscape model - Svatonova, H; Rybansky, M (IOP conference series. Earth and environmental science, 2014)
Visualizations supported by new geoinformation technologies prove to be appropriate tools for presenting and sharing the research results by professional and general public. The object of the research was to evaluate the benefits of visualizations for the nonexpert users. The subject of evaluation was: the success rate of interpreting the information; forming of a realistic idea of the unknown landscape; and the preference of the users during selection of the appropriate visualization for the purpose of solving the task. The tasks concerned: assessing the current situation and changes of the landscape; assessing the erosion in the landscape; and the ways of their visualizing. To prepare and process the landscape visualizations, it was necessary to select areas that allow tracking of land use changes and representative environmental processes. Then the digital landscape model was created and a number of visualizations were generated. The results of visualization testing show that the users prefer maps to orthophotos, they are able to formulate correct statements concerning the landscape with the help of visualizations, and that the simulated fly throughs represent a very suitable tool supporting formation of a realistic ideas about the landscape.